Characterization of pore structure and reservoir properties of tight sandstone with CTS, SEM, and HPMI: A case study of the tight oil reservoir in fuyu oil layers of Sanzhao Sag, Songliao basin, NE China - Mu, Changhe; Hua, Haojie; Wang, Xiukun (Frontiers in Energy Research, 2023)
Quantitative characterization of the pore throat structures and reservoir properties of the tight sandstone in Fuyu oil layers of Sanzhao Sag, Songliao Basin, NE China was carried out using cast thin section (CTS), scanning electron microscopy (SEM) and high-pressure mercury intrusion (HPMI) combined with fractal theory. CTS and SEM describe the composition, pore filling, cementation, and connectivity of tight sandstones. Six different fractal models, i.e. 2D capillary model, 3D spherical model, 3D capillary model, geometric model, thermodynamic model, and wetting phase model are used to calculate the fractal dimension of pore size distribution using capillary pressure data of HPMI, and their correlations with reservoir properties were analyzed. The images of CTS and SEM show that the main lithology of this oil reservoir is tight sandstone, and the pore types are mainly intergranular dissolved pores and intragranular dissolved pores, with uneven pore distribution and poor connectivity. The study of the HPMI data shows that the average pore radius is the main influencing factor of tight sandstone permeability. The fractal dimensions calculated from the HPMI capillary pressure data using the 3D capillary model and the wetting phase fractal model have the strongest correlations with the reservoir properties compared with the other fractal model. As the fractal dimension increases, the pore throat structures become more heterogenous and reservoir properties become poorer. For the wetting phase fractal model, the calculated fractal dimension is positively correlated with the heterogeneity of the pore throat structure of tight sandstone, which is contrary to the fractal theory and is not suitable for analyzing pore throat structures. The fractal dimensions calculated from the thermodynamic model have no obvious correlations with reservoir properties and cannot quantitatively characterize the heterogeneity of tight sandstone.